Options for Reforming the Finnish Tax System - Joumard, Isabelle (OECD Publishing, 2002)
This paper reviews the Finnish tax system and the scope for further tax reform. Finland is among the most egalitarian countries in the OECD and a high tax burden is required to finance the associated public spending. Nevertheless, capital and corporate income taxation was substantially and effectively reformed in the early 1990s, through significant rate cuts cum base broadening measures. But, despite income tax cuts since the mid-1990s, high taxes, especially on labour income, still hamper growth potential and distort economic behaviour. In this respect, the poor performance of the Finnish labour market is revealing. Tax reforms have a major role to play in improving the long-term performance of the Finnish economy. Though the scope is limited, the tax burden should be shifted as much as possible from labour to property and consumption, while the earned-income tax allowance should play a smaller role, enabling cuts in statutory rates. Redesigning social security contributions to ...
Keywords: Economics; Finland